Sports performance as a moderator of the relationship between coping strategy and emotional intelligence - Mitić, Petar (Array, 2020)
The aim of the study is to examine the moderating role of sports performance in the relationship between emotional intelligence (EI) and stress coping strategies. In a sample of 171 elite and 169 non-elite athletes, EI was found to be related to task-oriented strategies, and completely unrelated to emotion-oriented strategies. Sport performance moderates the relationship between managing and regulating emotions and using avoidant coping strategies, in a way that non-elite athletes with higher scores on this EI subscale are more likely to use distraction-oriented coping.